Fermentasi Ampas Kelapa menggunakan Trichoderma viride, Bacillus subtilis, dan EM4 terhadap Kandungan Protein Kasar dan Serat Kasar sebagai Bahan Pakan Alternatif Ikan [Fermentation Of Coconut Dregs Using Trichoderma viride, Bacillus subtilis, And EM4 Against Crude Protein And Crude Fiber As An Alternative Feed Ingredients For Fish] - Yudi Cahyoko; Hiprita Putri Karlina; Agustono Agustono (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Feed plays an important role in fish farming. Feed requirements achieve 60-70% of the cost of fish farming operations. Availability of feed with quality and sufficient quantity is aimed in increasing fish production. A very high feed prices due to artificial feed ingredients used are expensive and required in large quantities. Therefore, it is necessary to find alternatives to fish directly or indirectly obtaining appropiate and adequate nutrition needs to grow. The raw material content used for feed is coconut dregs (Cocos nucifera). The availability of the coconut dregs is abundant and potensial for fish feed ingredients. The coconut dregs is also one type or plantation waste which still has potential to be processed into the manufacture of fish feed. The coconut dregs flour can be processed by fermentation to improve quality. This study was aimed to determine the increase in crude protein content and a decrease in crude fiber content of coconut dregs fermented with Trichoderma viride; Bacillus subtilis and EM4. The research method was an experiment with Completely Randomized Design (CRD). The treatments used without the addition of microbes (P0), Bacillus subtilis 6% (P1), Trichoderma viride 6% (P2), and EM4 6% (P3) with 5 repeatitions each. The parameters observed were the content of crude protein and crude fiber after 7 days of fermentation. Data analysis used Analysis of Variance (ANOVA) and to determine the best treatments using Duncan Multiple Distance Test with 5% confidence interval. The results indicated that coconut dregs fermented with Bacillus subtilis (P1), Trichoderma viride (P2), and EM4 (P3) produced the difference of crude protein and fiber. The best treatment on the increase in crude protein content was Bacillus subtilis (P1) of 7.5564%. The best treatment on the decrease in crude fiber content was EM4 (P3) of 22.3967%. However, the results of the flour fermented coconut dregs can not be used as an alternative feed material because the fermented coconut dregs is not qualified for fish feed. This is due to a lack of crude protein and high crude fiber content.